Accuracy and Reliability of Stroke Diagnosis in the Pediatric Emergency Department. Issue 5 (May 2017) - Mackay, Mark T.; Yock-Corrales, Adriana; Churilov, Leonid; Monagle, Paul; Donnan, Geoffrey A.; Babl, Franz E.
Abstract : Background and Purpose—: Access to acute stroke interventions in the emergency department (ED) relies on correct clinical diagnosis. Our aims were to determine the accuracy and reliability of pediatric ED physician diagnosis of childhood stroke and other conditions presenting with brain attack symptoms. Methods—: Prospective study of consecutive children aged 1 month to 18 years presenting to the ED from June 2009 to December 2010 with focal neurological deficits. Accuracy (sensitivity, specificity, and receiver operator characteristic curves [ROCs]) and interrater agreement (κ) were determined, between ED physician diagnoses, as recorded in the electronic hospital administrative software system, and final neurological diagnosis, after completion of diagnostic work-up. Results—: Two-hundred eighty-seven children with 301 consecutive presentations were recruited. The most common final brain attack diagnoses included migraine in 84 children, first seizure in 48, Bell's palsy in 29, stroke in 21, and conversion disorders in 18 children. Sensitivity of ED physician stroke diagnosis was 62%, and specificity was 98% (ROC, 0.8). Inter-rater agreement for ED physician and final stroke diagnosis was substantial (κ=0.61). ED physician diagnostic accuracy and reliability was highest for Bell's palsy (ROC=0.98; κ=0.96), and lowest for central nervous system demyelination (ROC=0.5; κ=−0.01) and cerebellitis (ROC=0.50; κ=0.50). Conclusions—: ED physician diagnostic accuracy and reliability varies considerably across disorders presenting with brain attack symptoms. Clinical recognition tools are required to assist pediatric ED physicians with diagnosis of stroke and other serious neurological disorders.